2023
DOI: 10.3390/foods12102026
|View full text |Cite
|
Sign up to set email alerts
|

Edible Insects as a Novel Source of Bioactive Peptides: A Systematic Review

Abstract: The production of food and feed to meet the needs of the growing world’s population will soon become a serious challenge. In search for sustainable solutions, entomophagy is being proposed as an alternative source of proteins, with economic and environmental advantages when compared to meat. Edible insects are not only a valuable source of important nutrients, but their gastrointestinal digestion also originates small peptides with important bioactive properties. The present work intends to provide an exhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Most studies concerning the bioactive properties of edible insects focused on the identification of peptides with antihypertensive, antidiabetic and antioxidant properties. 13 In a previous work, we reported that insects can also be a source of bioactive peptides with antifibrosis properties. An in silico protocol that simulated gastrointestinal (GI) digestion of the house cricket ( Acheta domesticus ) identified several peptides capable of selectively inhibiting the N-subunit of the somatic angiotensin-I converting enzyme (sACE; EC 3.4.15.1).…”
Section: Introductionmentioning
confidence: 98%
“…Most studies concerning the bioactive properties of edible insects focused on the identification of peptides with antihypertensive, antidiabetic and antioxidant properties. 13 In a previous work, we reported that insects can also be a source of bioactive peptides with antifibrosis properties. An in silico protocol that simulated gastrointestinal (GI) digestion of the house cricket ( Acheta domesticus ) identified several peptides capable of selectively inhibiting the N-subunit of the somatic angiotensin-I converting enzyme (sACE; EC 3.4.15.1).…”
Section: Introductionmentioning
confidence: 98%
“…In Table 1, a list of bioactive peptides evaluated in vitro to potentially exhibit immunomodulatory properties is reported, indicating the methodology employed by the authors. Teixeira et al 26 recently carried out a systematic review aiming to identify research articles reporting bioactive peptides identified from edible insects, as demonstrated by in silico , in vitro , and/or in vivo assays.…”
Section: The Role Of Insect Peptides In Immunonutritionmentioning
confidence: 99%
“…Among the described bioactivities reported in the literature (antidiabetic, antioxidant, antithrombotic, etc . ), 25,26 the focus of this review will be on the immunomodulatory properties, generally associated with an anti-inflammatory character.…”
Section: Introductionmentioning
confidence: 99%
“…20,76 Farmed insects such as G. sigillatus , S. gregaria and B. mori have also been successfully hydrolyzed through gastrointestinal digestion and new bioactive peptides have been isolated. 5,77,78 Besides, microbial enzymes including alcalase, thermolysin, flavourzyme and acid protease were used for the hydrolysis of A. assamensis pupae and S. littoralis and T. molitor proteins. 30,70,79 However, only limited research reported the use of plant-derived enzymes like papain for producing insect protein hydrolysates.…”
Section: Insect Protein Hydrolysis and Bioactive Properties Of Insect...mentioning
confidence: 99%